Radiographic abnormalities in carcinoma of the lung as related to histological cell type - Byrd, R. B. (1969)
A detailed study was made of the chest radiographs of 600 patients with bronchogenic carcinoma who had had thoracotomy or intensive radiotherapy. Tumours of the various histological cell types tended to present with different radiographic patterns. Squamous-cell carcinoma was most often characterized by bronchial obstruction, often in association with a hilar mass. Squamous-cell lesions also were far more likely to show cavitation than were lesions of the other cell types. Small-cell carcinoma had a higher percentage of hilar masses than did other tumours but showed less tendency than did squamous-cell carcinoma to produce obstruction in association with the hilar mass. Adenocarcinoma most often presented as a peripheral mass as did large-cell carcinoma.